Les agglomérations de Germanie Seconde aux ive et ve s. apr. J.-C. - Raymond Brulet (Gallia)
The province of Germania Secunda is composted of “regiones”, some of which, to the west, are no more of interest in the Late Antiquity, due to the fact that their territory has been partly reduced by the marine Dunkirk transgression. At that time, the Rhine border is being abandoned by the army and the political centre at Nijmegen, in the Batavians territory, looses part of its importance. Xanten colony is confronted with tragic events in the mid 4th c. AD and to a drastic reduction of its ascendancy as a town. It is no doubt this situation that explains why the Notitia Dignitatum only mentions for the early 5th c. two civitates in this province. However, other issues occur: the exploitation of various resources on both sides of a west-east line, between silt and sand soils, depopulation which hits the greater portion of the province, and regular installation of new foreign communities. The clustered settlements are connected to two totally different spheres: a military zone along the limes, which during the High Empire favours the development of canabae and military vici ; the second one in the hinterland, composed of road networks confronted with successive periods of trouble during the Late Antiquity and small centres out of the road networks. The military agglomerations may be at the origin of the development of a new form of long lasting grouped settlements. On the other hand, the linear settlements survive on a short limited time. The hilltop sites in the south of the province cannot really be counted within the problematics concerning settlement. With the disparition of small towns, it cannot escape our notice that the province is tightening up settlements and activities inside real clusters surviving here and there for various reasons. But the best vehicle for habitat and economy is represented by the Meuse valley which runs across this political entity from north to south and shelters all the resources necessary for a continuous development of sites, many of which will form resilient towns.